Non-formal education and new partnerships in a (post-)conflict situation: 'Three cooking stones supporting one saucepan'. (May 2015) - van der Linden, Josje
Highlights: The combination of these two groups gives the organisation a strong base. YWCDO is filling a gap left by the government, but hardly acknowledged for it. Sustainability of the organisation is not a matter of course. The importance of human activity to bring people together. The women in the course make their own ' blend ' of Western and local knowledge. Abstract: The conviction is gaining ground that education, not only for children, but also for youth and adults, is vital in conflict-affected areas to (re)build a strong society. This article discusses the constructive role of non-formal education in a post-conflict situation. Concepts of international cooperation and partnerships on the one hand and non-formal education and lifelong learning on the other hand are used to build a framework for analysing a micro development project in a conflict-affected area in North-Western Uganda. The analysis highlights the dynamics that play a role when people collaborate in rebuilding their communities.